2020
DOI: 10.21203/rs.3.rs-90830/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Visceral Leishmaniasis Outbreaks in Bihar: Community-level Investigations in the Context of Elimination of Kala-azar as a Public Health Problem

Abstract: Background: With visceral leishmaniasis (VL) incidence at its lowest level since the 1960s, increasing attention has turned to early detection and investigation of outbreaks. Methods: Outbreak investigations were triggered by recognition of case clusters in the VL surveillance system established for the elimination program. Investigations included ascertainment of all VL cases by date of fever onset, household mapping and structured collection of risk factor data. Results: VL outbreaks were investigated in 13 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Given the many small and large outbreaks in the eight-year time window of KAMIS data, an appropriate threshold could be empirically derived and then prospectively tested. To date, initiation of outbreak investigations has required reporting of case clusters by astute local staff ( Priyamvada et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the many small and large outbreaks in the eight-year time window of KAMIS data, an appropriate threshold could be empirically derived and then prospectively tested. To date, initiation of outbreak investigations has required reporting of case clusters by astute local staff ( Priyamvada et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The well-documented clustering of VL cases at the village and sub-village levels provides the basis for developing ACD targeting strategies ( Bulstra et al., 2018 ; Chapman et al., 2020 ; Priyamvada et al., 2021 ). It is not possible to cover all villages in the affected districts of the affected states using any ACD method, particularly the more intensive ones such as house-to-house searches, since Bihar alone has more than 43,000 villages in 33 endemic districts.…”
Section: Introductionmentioning
confidence: 99%
“…Another behavioral habit that may be relevant to vector-transmission of L. donovani by Ph. argentipes in India is open defecation, which was associated with significantly elevated risk of VL in a recent investigation in Bihar ( Priyamvada et al., 2021 ). Despite government campaigns to change it, open defecation is still common in India, and represents one of the highest rates in the world.…”
Section: Knowledge Gaps Underpinning Failures In Vector Control Efformentioning
confidence: 99%
“…Prevalence is associated with malnutrition, population displacement, poor housing, a weak immune system, and poverty [3]. In a previous study in Bihar, residence in highly marginalized communities was found to be the greatest risk factor for being affected by VL [12].…”
Section: Introductionmentioning
confidence: 99%